2014
DOI: 10.1093/mnras/stu323
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of CHONS particles to the diffuse high-Galactic-latitude IR emission

Abstract: This work purports to model the far infrared gray-body emission in the spectra of high-Galactic-latitude clouds. Several carbonaceous laboratory materials are tested for their fitness as carriers of this modified-black-body emission which, according to data delivered by the Planck satellite, and others before, is best fit with temperature 17.9 K and spectral index β=1.78. Some of these materials were discarded for insufficient emissivity, others for inadequate β. By contrast, CHONS clusters (β = 1.4, T = 19 K)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The seduction of the coal model of UIE and the related petroleum fraction and asphaltene models which at the end can be collected into the more general MAONs model regards the fact that it does not exist a single reference spectrum but samples of both coal, petroleum fractions and asphaltenes can be selected at different degrees of "maturity" or ranks. It is possible, for instance, to start from a low rank coal that is richer in hydrogen content and aliphatics and by a thermal or radiation treatment reach a higher rank coal with lower hydrogen content and higher aromatic content (Papoular, 2013(Papoular, , 2014Cataldo & Keheyan, 2003;Cataldo, Keheyan & Baccaro, 2004). In parallel, also the organic matter in space -for example, as found around evolved stars such as asymptotic giant branch (AGB) stars and (proto-)planetary nebulae -responsible for the UIE undergoes a considerable evolution since its mixed aliphatic/aromatic ratio changes continuously, affecting the resulting UIE features.…”
Section: -Carbonization Of Selected Substrates To Match the Anthracit...mentioning
confidence: 99%
See 1 more Smart Citation
“…The seduction of the coal model of UIE and the related petroleum fraction and asphaltene models which at the end can be collected into the more general MAONs model regards the fact that it does not exist a single reference spectrum but samples of both coal, petroleum fractions and asphaltenes can be selected at different degrees of "maturity" or ranks. It is possible, for instance, to start from a low rank coal that is richer in hydrogen content and aliphatics and by a thermal or radiation treatment reach a higher rank coal with lower hydrogen content and higher aromatic content (Papoular, 2013(Papoular, , 2014Cataldo & Keheyan, 2003;Cataldo, Keheyan & Baccaro, 2004). In parallel, also the organic matter in space -for example, as found around evolved stars such as asymptotic giant branch (AGB) stars and (proto-)planetary nebulae -responsible for the UIE undergoes a considerable evolution since its mixed aliphatic/aromatic ratio changes continuously, affecting the resulting UIE features.…”
Section: -Carbonization Of Selected Substrates To Match the Anthracit...mentioning
confidence: 99%
“…Through spectral fittings of the astronomical spectra of the UIE, Kwok & Zhang (2011) have shown that a significant amount of the energy is emitted by the aliphatic component, implying that aliphatic groups are an essential part of the chemical structure. The MAON concept was also explored further by Papoular (2013Papoular ( , 2014. In the context of the petroleum fractions, and have shown that examples of naturally occurring MAONs can be represented by petroleum asphaltenes as well as asphaltenes derived by other fossil hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%